Comparison of techniques for left subclavian artery preservation during thoracic endovascular aortic repair: A systematic review and single-arm meta-analysis of both endovascular and surgical revascularization - Zhang, Yuchong; Xie, Xinsheng; Yuan, Ye; Hu, Chengkai; Wang, Enci; Zhao, Yufei; Lin, Peng; Li, Zheyun; Mo, Fandi; Fu, Weiguo; Wang, Lixin (Frontiers in Cardiovascular Medicine, 2022)
Background: Currently, the optimal technique to revascularize the left subclavian artery (LSA) during thoracic endovascular aortic repair (TEVAR) remains controversial. Our study seeks to characterize early and late clinical results and to assess the advantages and disadvantages of endovascular versus surgical strategies for the preservation of LSA. Methods: PubMed, Embase and Cochrane Library searches were conducted under the PRISMA (Preferred Reporting Items for Systematic review and Meta-Analyses) standards. Only literature published after January 1994 was included. Studies reporting on endovascular revascularization (ER), surgical revascularization (SR) for LSA preservation were included. 30-day mortality and morbidity rates, restenosis rates, and rates of early and late reintervention are measured as outcomes. Results: A total of 28 studies involving 2,759 patients were reviewed. All articles were retrospective in design. Single-arm analysis found no significant statistical differences in ER versus SR in terms of 30-day mortality and perioperative complication rates. The mean follow-up time for the ER cohort was 12.9 months and for the SR cohort was 26.6 months, respectively. Subgroup analysis revealed a higher risk of perioperative stroke (4.2%) and endoleaks (14.2%) with the chimney technique compared to the fenestrated and single-branched stent approaches. Analysis of the double-arm studies did not yield statistically significant results. Conclusion: Both ER and SR are safe and feasible in the preservation of LSA while acheiving an adequate proximal landing zone. Among ER strategies, the chimney technique may presents a greater risk of neurological complications and endoleaks, while the single-branched stent grafts demonstrate the lowest complication rate, and the fenestration method for revascularization lies in an intermediate position. Given that the data quality of the included studies were relatively not satisfactory, more randomized controlled trials are needed to provide convincing evidence for optimal approaches to LSA revascularization in the future.